Educação ambiental : concepções e práticas de professores de ciências do ensino fundamental - Oliveira, André Luis de (2006)
From the decade of 1980 onward, a review of science and its teaching has offered a more fertile ground for debates over the environment. It is in this context that the Environmental Education and the Science Teaching may contribute as much for the traditional teaching as for activities of the informal one. As far as a new evaluation of environmental questions is concerned in the science teaching while a constructive means of children and adolescents' opinion and who are or will be in contact with them, the present issue is proposed. Its goal is to identit)r the conceptions and the science teachers' pedagogical practice regarding to environmental education in the elementary school, arising from their speeches the possible contributions for the teaching of science in order make them aware of social and environmental questions. Therefore, eleven science teachers from elementary schools participated in this research, from fifth to eighth grade, from five state schools in Paraná State. In this perspective, through Oral History, the science teachers' experiences which set their scholastic process were recovered as well as their professional graduation and pedagogical practice, focusing on the environmental questions discussed in each interviewed teacher's life. It is easy to realize that most of the interviewed teachers do no have a clear concept about the environment. They emphasize the environment as the nature, the place where we live and from where we extract resources. Most of the reports portray the Environment in an anthropocentric view, whose source was in the humanistic anthropocentric ethics and in the Cartesian thought which places the man out of his natural environment. Regarding to the majority of the answers, the conceptions of the interviewed teachers are based on concepts or information that are commonly presented separated from a proposal of work which contributes to the formation of critical citizens, able to construct knowledge by means of changes in values and of an ethical posture before environmental questions. Finally, the analysis and data interpretation reflect that the environmental education will effectively be discussed with the relevancy it deserves when we, as science teachers, reach a degree of conscience and understanding of the interdisciplinary relations of the several fields of knowledge. Thus, a reflection on our conceptions, attitudes and pedagogical practice in classroom is required.